Relationship Marketing Between Hydroponic Farmers And Buyers (Case Study Of Mardika Ambon Market) - Resfilgha Gloria Sahupala; S.F.W.Thenu; M.T.F.Tuhumury (Cita konsultindo, 2023)
The purpose of this research is to describe how relationship marketing between hydroponic farmers and the Mardika Ambon market, and determine the type of relationship marketing. This research uses quantitative analysis and qualitative analysis, and uses a Likert scale to measure the level of trust and commitment of the Mardika market. The results showed that relationship marketing between hydroponic farmers and Mardika market has low trust and commitment due to high oppurtunistic value, low value sharing, low disconnection cost, high functional conflict and high uncertainty. and is included in the transactional relationship marketing type.